Th22 cells are associated with hepatocellular carcinoma development and progression - Qin, Shanyu; Ma, Shijia; Huang, Xiaoli; Lu, Donghong; Zhou, You; Jiang, Haixing (Chinese Journal of Cancer Research, 2014)
Objective: IL-22-producing CD4+ T helper cells (Th22 cells) have been identified as major inducers of tissue inflammation and immune responses. Currently, no previous study explored the role of Th22 cells in the pathogenesis of hepatocellular carcinoma (HCC). The study aimed to determine the biological function of Th22 cells and its effector IL-22 in HCC patients. Methods: Forty-five HCC patients and 19 healthy controls were recruited and their peripheral blood was collected. The fresh HCC tissues, adjacent HCC tissues and ten normal liver tissues were also collected. Flow cytometry analysis was used to determine the frequencies of circulating Th22 cells and Th17 cells. Serum IL-22 levels were tested by enzyme-linked immunosorbent assay (ELISA). Immunohistochemical staining and real-time polymerase chain reaction (PCR) were used to detect IL-22 protein and mRNA in tissues specimens, respectively. Results: Circulating Th22 cells, Th17 cells and serum IL-22 levels were significantly elevated in HCC patients compared with those of healthy controls (P